The prognostic impact of gender in patients with acute heart failure – An evaluation of the age of female patients with severely decompensated acute heart failure. Issue 3 (September 2017) - Nozaki, Ayaka; Shirakabe, Akihiro; Hata, Noritake; Kobayashi, Nobuaki; Okazaki, Hirotake; Matsushita, Masato; Shibata, Yusaku; Nishigoori, Suguru; Uchiyama, Saori; Kusama, Yoshiki; Asai, Kuniya; Shimizu, Wataru
Abstract: Background: The gender differences in the prognosis of Asian patients with acute heart failure (AHF) remain to be elucidated. Methods and results: One thousand fifty AHF patients were enrolled. The patients were assigned to a female group ( n  = 354) and a male group ( n  = 696). A Kaplan–Meier curve showed that the cardiovascular survival rate of the female group was significantly lower than that of the male group ( p  = 0.005). A multivariate Cox regression model identified female gender [hazard ratio (HR): 1.381, 95% CI: 1.018–1.872] as an independent predictor of 730-day cardiovascular death. In subgroup analysis by age, in patients over 79 years, female gender significantly increased the cardiovascular death (HR: 1.715, 95% CI: 1.088–2.074, p  < 0.001) with a significant interaction ( p -value for interaction < 0.001). The prognosis, including cardiovascular death, was significantly poorer among elderly female patients (≥79 years) than among elderly male patients ( p  = 0.019). The multivariate Cox regression model identified female gender as an independent predictor of 730-day cardiovascular death in patients who were older than 79 years of age (HR, 1.943; 95% CI, 1.192–3.167). Conclusions: Female gender was associated with poor prognosis in AHF patients. In particular, old age (≥79 years) was associated with adverse outcomes in female patients with AHF.